Data Protection - Perú - Reátegui Valdiviezo, Maritza (Revista de Derecho, 2019)
The present article refers to the implementation of the Protection of Testing Data forpharmaceutical products in the light of the implementation of the FTA signed by Peruand the United States of America and the application of the definitions given by theTRIPS for this figure. The national legislation and the applicable treaties are analyzedas well as the first cases of protection to the new chemical entities given by the regulatoryauthority. The successes and drawbacks of the new Testing Data legislation. Theirimpact on heath and research issues.
Keywords: data protection; Data exclusivity; clinical studies; Pharmaceutical Law; Pharmaceutical products